Integrative and cognitive approach to teaching of foreign medical students to take down lectures on speciality - V. D. Kheylik (Zaporožskij Medicinskij Žurnal)
The article is devoted to some aspects of the effectiveness of the language training for medical higher school foreign students. Special attention is given to a new technological approach in teaching foreign students to make notes of the medical and biological profile lectures.